Women, travel and identity : Journeys by rail and sea, 1870-1940 - Robinson-Tomsett, Emma (Gender in history., 2013)
Between 1870 and 1940, a period of dramatic social, cultural and technological change, millions of British women journeyed abroad on steamships and trains, motivated by economic need, a desire to start a new life, faith, health, love, curiosity or sheer necessity. Women, travel and identity explores their experiences as journey consumers - experiences that have remained largely hidden until now, despite the journey being the most universal female travel experience of the period. Drawing upon diaries and letters, art, advertising, fiction and etiquette guides, it examines the journey's impact upon women's identities and definitions of femininity, modernity, glamour, class, travel, tourism, leisure and sexual opportunity and threat. The book explores women's relationship with train and ship technology, as well as cultural understandings and public expectations of the journey. Robinson-Tomsett also explores how women journeyed in practice, examining their use of journey space, their sociability with both Western and 'Other' non-Western journeyers, and their experience of love, sex and danger during the journey. She highlights the ways in which women fashioned a journeyer identity which fused their existing domestic identities with new identities such as the journey chronicler. It will appeal to academics, postgraduates and undergraduates studying women's and gender history; travel, transport and mobility studies; Victorian, cultural and leisure history; and postcolonial and feminist studies, as well as enthusiasts of what is considered a 'golden age' of travel featuring some of the greatest transport ever built, including the Orient Express and the Titanic.